Psychology at the heart of social change : developing a progressive vision for society - Cooper, Mick (Policy Press, an imprint of Bristol University Press, 2023)
This book shows why we need, and can create, a progressive politics that is profoundly informed by insights from the psychotherapeutic and psychological domain, moving us from a politics of blame to a politics of understanding.